The assumption of uniform specific discharge: unsafe at any time?. Issue 21 (15th June 2016) - Karlsen, R. H.; Seibert, J.; Grabs, T.; Laudon, H.; Blomkvist, P.; Bishop, K.
Abstract: Nearby catchments in the same landscape are often assumed to have similar specific discharge (runoff per unit catchment area). Five years of streamflow from 14 nested catchments in a 68 km 2 landscape was used to test this assumption, with the hypothesis that the spatial variability in specific discharge is smaller than the uncertainties in the measurement. The median spatial variability of specific discharge, defined as subcatchment deviation from the catchment outlet, was 33% at the daily scale. This declined to 24% at a monthly scale and 19% at an annual scale. These specific discharge differences are on the same order of magnitude as predicted for major land‐use conversions or a century of climate change. Spatial variability remained when considering uncertainties in specific discharge, and systematic seasonal patterns in specific discharge variation further provide confidence that these differences are more than just errors in the analysis of catchment area, rainfall variability or gauging. Assuming similar specific discharge in nearby catchments can thus lead to spurious conclusions about the effects of disturbance on hydrological and biogeochemical processes. Copyright © 2016 John Wiley & Sons, Ltd.